Aspects of labour welfare and social security - Sarma, A. M. (Mumbai, 2006)
Aspects of Labour Welfare and Social Security' is in two parts. Part I deals with labour welfare and Part II covers social security. The book contains altogether 24 chapters and 5 appendices. The book presents the material in a simple and lucid style for easy understanding of the subject. It is addressed mainly to meet the needs of students and practitioners.
Keywords: Labour welfare